Model Analisis Solvabilitas, Aktifitas dan Profitabilitas Terhadap Nilai Pasar Saham dengan Share Traded sebagai Variabel Intervening pada Perusahaan Sub Sektor Food And Baverages di Bursa Efek Indonesia Periode 2014 – 2019 - Siti Nur Ambarini; Yunan Surono (Universitas Batanghari, 2021)
This study is to look at the performance of food and baverages companies, by looking at the relationship between solvency variables, activities, and profitability to the stock market value with share traded as intervening variables in the food and baverages sub-sector on the Indonesia Stock Exchange during the period 2014-2019. This study uses the first free variable which is a solvency variable that is projected with debt to asset ratio indicator and debt to equity ratio. This study uses the second free variable which is the activity variable that is projected with total asset turnover, fixed asset turnover and inventory turnover. The third free variable is the profitability variable that is projected with indicators of return on asset, return on equity, net profit margin and gross profit margin. Bound variables are variable stock market value that is projected with price earning ratio indicator, price book value, and earning per share. Intervening variable is share traded with indicator volume traded, value traded, frequency traded and days traded. The research sample used is a group of food and baverages sub-sector stocks during the 6-year observation period, starting from 2014 - 2019, which has financial statements with complete research indicators, financial statements using the value of rupiah currency, namely as many as 16 issuers. This research is in the form of explanatory research and data analysis using Partial Least Square using Smart PLS 3.0 software The results show, solvency variables have no effect on share traded, activity variables affect share traded, profitability variables have no effect on share traded, solvency variables have no effect on stock market value, activity variables have no effect on stock market value, profitability variables affect stock market value, solvency variables have no effect on the value of the stock market, activity variables have no effect on the value of the stock market with share traded as intervening variables, profitability variables have no effect on the value of the stock market with share traded as intervening variables, share traded variables have no effect on the value of the stock market.